2004
DOI: 10.1111/j.1365-2044.2004.03858.x
|View full text |Cite
|
Sign up to set email alerts
|

The accuracy of trained nurses in pre-operative health assessment: results of the OPEN study

Abstract: SummaryWe quantified the accuracy of trained nurses to correctly assess the pre-operative health status of surgical patients as compared to anaesthetists. The study included 4540 adult surgical patients. Patients' health status was first assessed by the nurse and subsequently by the anaesthetist. Both needed to answer the question: 'is this patient ready for surgery without additional work-up, Yes ⁄ No?' (primary outcome). The secondary outcome was the time required to complete the assessment. Anaesthetists an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
30
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(31 citation statements)
references
References 26 publications
1
30
0
Order By: Relevance
“…To get an impression of the recent developments in preoperative evaluation and to be able to make thorough questions for the face-to-face interviews, Pubmed and EBSCOhost ® Academic Search Elite databases were used to search for literature concerning the organization, implementation and cost-effectiveness of preoperative evaluation in hospitals. The literature which was selected consisted of studies on (guidelines for) preoperative evaluation by anaesthesiologists and on OPE clinics [1][2][3][4][5][6][7][12][13][14][15][16][17]. In this, special attention was paid to the study of van Klei and colleagues, which was considered as the pilot study of the present study.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To get an impression of the recent developments in preoperative evaluation and to be able to make thorough questions for the face-to-face interviews, Pubmed and EBSCOhost ® Academic Search Elite databases were used to search for literature concerning the organization, implementation and cost-effectiveness of preoperative evaluation in hospitals. The literature which was selected consisted of studies on (guidelines for) preoperative evaluation by anaesthesiologists and on OPE clinics [1][2][3][4][5][6][7][12][13][14][15][16][17]. In this, special attention was paid to the study of van Klei and colleagues, which was considered as the pilot study of the present study.…”
Section: Methodsmentioning
confidence: 99%
“…Literature about the most recent development regarding OPE clinics in Dutch hospitals, namely the employment of nurses substituting anaesthesiologists, was also taken into account [15,17].…”
Section: Methodsmentioning
confidence: 99%
“…He explains, "Two articles are particularly important, one in 2002 in Anesthesia and Analgesia 5 and one in 2004 in Anaesthesia, 6 for which we developed a preoperative clinic and then showed that it led to fewer cancellations. It is better for people to come to our clinic before surgery so we have time to assess and educate them."…”
Section: "We Found a Strong Association Between Postoperative Myocardmentioning
confidence: 99%
“…We have continually refined our practice to ensure that high-risk patients have a better chance of surviving major surgery [5]. We have been open and enquiring to new ways of working in multi-disciplinary partnerships [6,7], and we have gone back to the laboratory to consider the basic building blocks of our science [8,9]. We have fearlessly re-examined the sacred cows taught us by our predecessors, and discarded them where evidence is lacking or outcomes perverse [10][11][12].…”
mentioning
confidence: 99%